Europe at the crossroad of the Covid-19 crisis: Integrated macroeconomic policy solutions for an asymmetric area - Vale, S.; Mendonça, A. (New challenges for the eurozone governance: Joint solutions for common threats?, 2021)
The economic crisis triggered by the COVID–19 pandemics raised once again doubts about the eurozone's ability to deal with common serious economic problems. The effects of the 2008 – 2009’s economic and financial crisis have not been completely exhausted, and a new crisis of yet unknown proportions emerged, bringing with it the traditional divergences between a common and integrated approach to problems and a country-based approach conditioned by Euro Area restrictive and asymmetric macroeconomic rules. This chapter aims at contributing to a paradigm shift in the governance of the eurozone towards a less dominant tendency for ruling according to the interests of the most powerful economies, namely Germany, and to a more comprehensive and integrated approach of the eurozone dissimilar dynamics and asymmetries, including the case of small economies like Portugal. Two dimensions of this need for a new paradigm of eurozone governance are considered. Firstly, the need for a change in the economic policy concerning the crisis recovery, from a supply-push to a demand-pull orientation, supported on a fiscal and monetary policy mix, integrated in a comprehensive macroeconomic approach. It is important to recognize the role of the ECB since the 2008 – 2009’s crisis and in the current context but also the need for a more active intervention of fiscal policy, both converging towards a growth-oriented policy. Secondly, the need for a shift in external relations towards a more global integration-oriented policy, with the Eurozone positioning itself as an alternative to the current polarization between the United States and China. Our conclusions point to the need to i) give priority to growth and employment; ii) promote long-term economic sustainability based on integrated macroeconomic policies, the reduction of income concentration and the reconstitution of strong middle classes; iii) reorientate international relations into a perspective of cooperation; iv) reinforce regulation and global governance; and v) eliminate exceptional situations, such as offshores, tax havens and other forms of economic controls escape.